2020
DOI: 10.3389/fpsyt.2020.00289
|View full text |Cite
|
Sign up to set email alerts
|

Prosocial Behavior Can Moderate the Relationship Between Rumination and Mindfulness

Abstract: Objective: Rumination, which is a coping style to distress, has become a common mode of thinking about mental illnesses such as depression and anxiety. Improving mindfulness is an effective way to help people cope with rumination. Individuals who had higher prosocial behaviors reported a high level of mindfulness. This study aimed to explore whether prosocial behavior helps individuals with high-level rumination improve their mindfulness, and explain the reason why prosocial behavior can influence the relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…Results from the mediation analysis confirmed that prosocial behavior negatively mediated the relationship between gratitude and negative aspects of mental health. These results were consistent with a recent literature given by Meng and Meng (2020) stated that improving gratitude is an effective way to help people cope with the negative aspects of mental health. Individuals who had lower prosocial behavior reported high level of depression and anxiety.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Results from the mediation analysis confirmed that prosocial behavior negatively mediated the relationship between gratitude and negative aspects of mental health. These results were consistent with a recent literature given by Meng and Meng (2020) stated that improving gratitude is an effective way to help people cope with the negative aspects of mental health. Individuals who had lower prosocial behavior reported high level of depression and anxiety.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies also stated that gratitude may influence people to repay a favor by engaging in prosocial behavior. Studies have determined that prosocial behavior can also improve the mental health problems (Grant & Gino, 2010;Meng & Meng, 2020).…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…The active momentum limits the opportunities for remorse and self-criticism and the sense of stalemate and blockage (Klein and Epley, 2014;Futamura, 2018;Leder et al, 2020;Shi et al, 2020). As pointed out by Meng and Meng (2020), encouraging prosocial behavior is also an effective way to improve mindfulness in highly ruminative individuals.…”
Section: English Version Italian Versionmentioning
confidence: 99%
“…For example, in one study, 15 min of online positive affect journaling three times a week for 12 weeks reduced mental distress and increased wellbeing (Smyth et al, 2018). Prosocial behaviour has also been shown to help diminish rumination by improving mindful awareness and attention to the present (Meng & Meng, 2020). Focusing on helping other people in need allows one to disengage from one's own thoughts and emotions and invest one's cognitive resources elsewhere.…”
Section: Discussionmentioning
confidence: 99%